The effect of binary antioxidant proportions on antioxidant synergy and oxidation stability of Jatropha and Karanja biodiesels. (1st May 2015) - Rawat, Devendra S.; Joshi, Girdhar; Lamba, Bhawna Y.; Tiwari, Avanish K.; Kumar, Pankaj
Abstract: Oxidation has been measured a major problem for biodiesel commercialization. Auto-oxidation takes place when exposed to air, heat, light and metallic contaminants which affects adversely the fuel characteristics of biodiesel. Addition of synthetic antioxidants generally improves the oxidation stability of biodiesel; however the use of large concentration of additives makes the process uneconomical. This study investigates the effectiveness of individual as well as binary antioxidants to improve the oxidation stability of Jatropha and Karanja biodiesels. Antioxidant synergy was investigated using 500, 600 and 700 ppm of antioxidant combinations namly Pyrogallol:Propyl gallate (PY:PrG), Pyrogallol:tert-butyl hydroquinone (PY:TBHQ) and Pyrogallol:Butylated hydroxyanisole (PY:BHA) at weight ratios of 9:1, 3:1, 2:1, 1:1, 1:2, 1:3 and 1:9, respectively. It was observed that higher blends of binary mixture produced negative synergy, however the best antioxidant synergy showed by the binary systems of PY:PrG, and PY:TBHQ, when the additives are mixed at 1:3 weight ratios; whereas binary mixture of PY:BHA resulted in complete antagonism. However, the effectiveness of the binary system on oxidation stability was found in order of 1:3/3:1 > 1:2/2:1 > 1:1 > 1:9/9:1. The efficacy of antioxidant combinations was evaluated by using pressurized PetroOXY method. Further the dependency of oxidation stability and antioxidant synergy on the fatty acid composition of biodiesel was also observed. Highlights: Effect of the addition of binary antioxidants on oxidation stability of biodiesel. Dependency of oxidation stability on the fatty acid profile of biodiesel. Binary mixture was found more effective in comparison to individual antioxidants. % Synergy decreases with increase in concentration of binary mixture. 1:3 weight ratios of PY:PrG and PY:TBHQ were found most effective among all.